2021
DOI: 10.1177/1066896921999459
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Brenner Tumor of the Ovary Coexisting With an Ovarian Mucinous Cystadenoma With Focal Atypical Epithelial Proliferation: A Rare Case With Review of the Literature

Abstract: Ovarian Brenner tumors, accounting for ∼5% of overall ovarian epithelial neoplasm, are often reported in association with mucinous neoplasm. Histogenetically, the two tumors are thought to arise from similar precursors. To date, fewer than 60 borderline Brenner tumors alone have been reported, and the concomitant presence of atypical proliferative components in Brenner and mucinous tumors is even rarer. Therefore, the clinicopathological characteristics and prognosis of patients with the borderline Brenner tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Based on histogenesis, the aforementioned tumors are believed to originate from analogous precursors. 19 , 20 The pathological evaluations of the patient in the present study demonstrated that a Brenner tumor is associated with mucinous metaplasia, similar to the findings of previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on histogenesis, the aforementioned tumors are believed to originate from analogous precursors. 19 , 20 The pathological evaluations of the patient in the present study demonstrated that a Brenner tumor is associated with mucinous metaplasia, similar to the findings of previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…6 Less than 60 studies regarding borderline Brenner tumors have been published to date, and there is minimal information regarding the favorable prognosis of the aforementioned tumors alone or with mucinous neoplasms. 19 In clinical practice, detecting tumors in the early stages is essential by employing strategies for early diagnosis and early treatment. 3 The patient of the current study was followed up for 2 years after the surgery, in which no complication was reported.…”
Section: Discussionmentioning
confidence: 99%
“…As for the choice of surgical methods, 72.0% (18/25) were treated with total laparoscopic hysterectomy and 24.0% (6/25) with salpingooophorectomy laparoscopy. Moreover, 4% (1/25) of the patients chose open surgery, which was inconsistent with the literature reports (31). The reason may be the large size of the tumor and the presence of potential malignancy.…”
Section: Discussionmentioning
confidence: 83%
“…Histologically, the borderline BT exhibit a characteristic papillary arrangement of uniform stratified neoplastic cells with oval nuclei possessing longitudinal grooves. They further demonstrate a fibro-vascular core and the absence of stromal invasion [ 4 - 6 ]. This histological presentation resembles low-grade papillary urothelial neoplasms [ 1 , 7 ] and frequently includes areas with a benign Brenner component [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%